Trends in diabetes medication use in Australia, Canada, England, and Scotland: a repeated cross-sectional analysis in primary care - Greiver, M; Havard, A; Bowles, JK; Kalia, S; Chen, T; Aliarzadeh, B; Moineddin, R; Sherlock, J; Hinton, W; de Lusignan, S; Sullivan, F; O'Neill, B; et al. (Royal College of General Practitioners, 2021)
Background Several new classes of glucose-lowering medications have been introduced in the past two decades. Some, such as sodium-glucose cotransporter 2 inhibitors (SGLT2s), have evidence of improved cardiovascular outcomes, while others, such as dipeptidyl peptidase-4 inhibitors (DPP4s), do not. It is therefore important to identify their uptake in order to find ways to support the use of more effective treatments.